Use of Complementary Health Approaches for Acute Complaints Presenting to the Emergency Department. Issue 7 (July 2020) - Kalaichandran, Amitha; Barrowman, Nick; Chan, Jason; Toupin-April, Karine; Vohra, Sunita; Zemek, Roger
Abstract : Objective: This study aimed to determine the prevalence of complementary health approaches (CHAs) specifically for acute complaints in patients assessed in a pediatric emergency department (ED) and factors associated with use. Methods: A cross-sectional survey was offered to patients between the age of 28 days and 18 years assessed at a tertiary pediatric ED between December 2014 and July 2015. Univariate and multivariate logistic regressions were used to identify variables associated with CHA use. Results: Of 475 potential participants, 412 (86.7%) participated, of which 369 (89.5%) completed the survey. Overall, 28.7% (95% confidence interval [CI], 24.3–33.5) reported using any CHA for their child to treat the presenting complaint in the prior 72 hours to the ED visit. Gastrointestinal complaints had the highest use of CHA (46.3% of presentations endorsed use). The most common complementary health products used were vitamins and minerals (40.9%; 95% CI, 31.2–51.4); the most common complementary health practice used was massage (37.2%; 95% CI, 24.4–52.1). Multivariate analysis showed lower odds of using CHA for rash/skin complaint (odds ratio, 0.23; 95% CI, 0.09–0.59; P < 0.01) or musculoskeletal/extremity complaints (odds ratio, 0.23; 95% CI, 0.07–0.75; P = 0.01) compared with use for fever. No statistically significant association was found between CHAs use and child's sex, child's age, private insurance, or caregiver education. Conclusions: Caregivers commonly use CHA for acute pediatric complaints requiring an ED visit, with greatest use for gastrointestinal complaints. Clinicians should consider the use and safety of CHA when evaluating children presenting to the ED with acute conditions.